Menurunkan Fenomena Gunung Es “Shaken Baby Syndrome” - Mirta, Surya Bin; Yuliani, Ita; Yulindawati, Asworoningrum; Dumilah, Retno (FORIKES, 2025)
Shaken Baby Syndrome (SBS) is a form of head trauma due to physical violence that causes brain damage, subdural hematoma, and long-term neurological complications. The purpose of this study was to determine evidence-based SBS prevention strategies, in order to fill the information gap and provide preventive policy recommendations in child health services. This study was a literature review by collecting articles from the PubMed database published between 2020 and 2024, with keywords related to SBS prevention. Furthermore, 8 relevant articles were obtained based on the inclusion criteria. The results of the review showed that educational programs have been shown to reduce the incidence of SBS by 30%. In Egypt and India, educational programs were effective in increasing knowledge about SBS prevention, although there are barriers to access to education in remote areas. Early detection is very important, with symptoms such as vomiting and seizures as the first signs of SBS. In Sweden, a policy of educating parents during pregnancy significantly reduced the incidence of SBS. It was concluded that training and awareness programs have been shown to be effective in reducing the incidence of SBS.Keywords: shaken baby syndrome; education; prevention ABSTRAK Shaken Baby Syndrome (SBS) merupakan salah satu bentuk trauma kepala akibat kekerasan fisik yang menyebabkan kerusakan otak, hematoma subdural, dan komplikasi neurologis jangka panjang. Tujuan dari studi ini adalah mengetahui strategi pencegahan SBS yang berbasis bukti, guna mengisi kesenjangan informasi dan memberikan rekomendasi kebijakan preventif dalam pelayanan kesehatan anak. Studi ini merupakan tinjauan literatur dengan mengumpulkan artikel dari basis data PubMed yang diterbitkan antara tahun 2020 sampai 2024, dengan kata kunci yang terkait dengan pencegahan SBS. Selanjutnya didapatkan 8 artikel relevan berdasarkan kriteria inklusi. Hasil tinjauan menunjukkan bahwa program pendidikan terbukti mengurangi kejadian SBS hingga 30%. Di Mesir dan India, program pendidikan efektif dalam meningkatkan pengetahuan tentang pencegahan SBS, meskipun terdapat hambatan akses pendidikan di daerah terpencil. Deteksi dini sangat penting, dengan gejala seperti muntah dan kejang sebagai tanda pertama SBS. Di Swedia, kebijakan mendidik orang tua selama kehamilan secara bermakna mengurangi kejadian SBS. Disimpulkan bahwa program pelatihan dan peningkatan kesadaran terbukti efektif dalam mengurangi kejadian SBS.Kata kunci: shaken baby syndrome; pendidikan; pencegahan